2017
DOI: 10.1371/journal.pone.0169807
|View full text |Cite
|
Sign up to set email alerts
|

Same Day Discharge versus Overnight Stay in the Hospital following Percutaneous Coronary Intervention in Patients with Stable Coronary Artery Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundNew research in interventional cardiology has shown the demand for percutaneous coronary interventions (PCI) to have increased tremendously. Effective treatment with a lower hospital cost has been the aim of several PCI capable centers. This study aimed to compare the adverse clinical outcomes associated with same day discharge versus overnight stay in the hospital following PCI in a population of randomized patients with stable coronary artery disease (CAD).MethodsThe National Library of Medicine (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
3
28
0
2
Order By: Relevance
“…Our study builds on and extends an accumulating body of evidence showing that SDD is safe and associated with lower costs of care. Two recent meta‐analyses of randomized controlled trials of SDD have confirmed the safety of SDD in terms of adverse events, such as mortality, myocardial infarction, major bleeding, blood transfusion, repeated revascularization, and rehospitalization; these adverse events were not significantly different between SDD and overnight stay groups, up to 30 days after PCI 3, 32. In the current climate of healthcare reform, lower costs of care offer a tremendous competitive advantage to hospitals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our study builds on and extends an accumulating body of evidence showing that SDD is safe and associated with lower costs of care. Two recent meta‐analyses of randomized controlled trials of SDD have confirmed the safety of SDD in terms of adverse events, such as mortality, myocardial infarction, major bleeding, blood transfusion, repeated revascularization, and rehospitalization; these adverse events were not significantly different between SDD and overnight stay groups, up to 30 days after PCI 3, 32. In the current climate of healthcare reform, lower costs of care offer a tremendous competitive advantage to hospitals.…”
Section: Discussionmentioning
confidence: 95%
“…Two recent meta-analyses of randomized controlled trials of SDD have confirmed the safety of SDD in terms of adverse events, such as mortality, myocardial infarction, major bleeding, blood transfusion, repeated revascularization, and rehospitalization; these adverse events were not significantly different between SDD and overnight stay groups, up to 30 days after PCI. 3,32 In the current climate of healthcare reform, lower costs of care offer a tremendous competitive advantage to hospitals. There is a constant and increasing pressure on the US healthcare system to reduce costs of care, and hospitals are increasingly challenged to deliver higher-quality care at lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…While complications are generally rare after elective PCI, when they do occur, they usually do so in the first few hours after PCI, facilitating the identification of patients who are unsafe for SDD. 3,4,8,[18][19][20] The practice of overnight observation for all patients after elective PCI for the concern for patient safety is not evidence based. Several randomized clinical trials have confirmed the safety of SDD vs NSDD.…”
Section: Discussionmentioning
confidence: 99%
“…Bundhun et al . have found that there are no significant differences in adverse outcomes between same day discharge and overnight hospital stay 8 . Therefore, a better explanation of the changes in PWTT of CAD patients, especially between before and after PCI, is helpful to understand the effectiveness of PCI.…”
Section: Introductionmentioning
confidence: 95%